DETERMINING THE DROUGHT TOLERANCE OF WINE GRAPE VARIETIES USING PEG-6000-INDUCED OSMOTIC STRESS - Fayziev Jamoliddin Nasirovich; Kurbanova Sarvinoz Anvar kizi; Xasanova Oyxanum Adilbekovna (Modern American Journals, 2025)
In the article, the drought tolerance of the grape varieties Plechistik and Muscat Yursky is evaluated under in vivo conditions using different concentrations (0%, 2%, 4%, 6%) of PEG-6000 (polyethylene glycol). The cuttings were studied based on shoot and root development indicators, biomass parameters, chlorophyll content, leaf turgor weight, and tolerance indices. The results showed that as the PEG concentration increased, all vegetative and physiological parameters of the plants significantly decreased, with the 4% and 6% PEG concentrations causing the strongest stress responses. The findings of the study provide an important basis for selecting and breeding drought-tolerant grapevine varieties.
Keywords: PEG-6000, grape, varity,stress of drought, shoot growth, rooting rate, physiological parameters, drought tolerance, in vivo, breeding.